WNK1 is required for proliferation induced by hypotonic challenge in rat vascular smooth muscle cells - ZHANG Ya-juan; ZHENG Hua-qing; CHEN Bao-yi; SUN Lu; MA Ming-ming; WANG Guan-lei; GUAN Yong-yuan (Acta Pharmacologica Sinica, 2017)
Abstract Hypotonic challenge evoked vascular cell proliferation through activation of volume-regulated Cl– channel (VRCC), leading to a decrease in the intracellular Cl– concentration ([Cl–]i). We hypothesize that the decrease in [Cl–]i may activate one or several Cl–-sensitive kinases, resulting in a subsequent signaling cascade. In this study we demonstrated that WNK1, a Cl–-sensitive kinase, was involved in VRCCinduced proliferative signaling pathway in A10 vascular smooth muscle cells in vitro. A10 cells were exposed to a hypotonic challenge (225 mosmol·kg-1·H20), which caused significantly increase in WNK1 phosphorylation without altering WNK1 protein expression. WNK1 overexpression significantly increased hypotonic-induced A10 cell proliferation, whereas silencing of WNK1 caused an opposite action. WNK1 mutation did not affect hypotonic-induced WNK1 phosphorylation and cell proliferation. Silencing of WNK1 caused cell cycle arrest at G0/G1 phase and prevented transition from G1 to S phase, whereas the WNK1 overexpression accelerated cell cycle transition from G1 to S phase. Silencing of WNK1 significantly inhibited cyclin D1/cyclin E1 expression and increased p27KIP/p21CIP expression. WNK1 overexpression significantly increased cyclin D1/cyclin E1 expression and reduced p27KIP/p21CIP expression. In addition, WNK1 knockdown or overexpression significantly attenuated or increased the hypotonic-induced phosphorylation of Akt and PI3K respectively. In conclusion, the reduction in [Cl–]i caused by hypotonic challenge-induced VRCC opening evokes WNK1 phosphorylation in A10 VSMCs, which mediates cell cycle transition from G0/G1 to S phase and proliferation through the PI3K-Akt signaling pathway.